Study of ansamycin inhibition of a ribonucleic acid-directed deoxyribonucleic acid polymerase by an immobilized template assay. - Milavetz, B I (1978)
A series of structurally related ansamycins have been analyzed, in a new immobilized template assay, to determine the mechanism by which they inhibit a ribonucleic acid-directed deoxyribonucleic acid (DNA) polymerase from Moloney murine leukemia virus. By this assay, we can better correlate specific structures of these drugs with inhibitory mechanisms. Using an immobilized template, we were also able to observe drug effects on the stability of complexes formed between the polymerase, a template (polyadenylic acid-agarose), and a primer, as well as to monitor the synthesis of DNA in the presence of drug. For each drug, we determined the complex (intermediate in DNA synthesis) which was primarily affected and whether the effect was due to a destabilization process. Although the activity and specificity of the unsubstituted ansamycins (streptovaricins and rifamycin SV) were modulated by conformation of the molecule and electron density of the aromatic ring, the principal mode of inhibition is, apparently, drug binding to a polymerase-template complex; the drug binds in a manner which prevents subsequent formation of a polymerase-template-primer complex. However, some derivatives of rifamycin SV, when substituted at carbon-3 with bulky or hydrophobic side chains, displayed markedly different modes of action. For example, demethyl dimethyl rifampin prevented the formation of polymerase-template complexes, whereas rifazacyclo 16 acted by promoting the dissociation of polymerase-template-primer complexes.